Known-Groups and Convergent Validity of the Telephone Rey Auditory Verbal Learning Test total Learning Scores for Distinguishing Between Older Adults With Amnestic Cognitive Impairment and Subjective Cognitive Decline. (17th October 2020) - Jagtap, Shreya; Dawson, Deirdre R; Vandermorris, Susan; Anderson, Nicole D; Davids-Brumer, Naomi; Dar, Mishal; Bernick, Alana; Rotenberg, Shlomit
Abstract: Objective: To examine known-groups validity of a telephone administration of the total learning scores of the Rey Auditory Verbal Learning Test (RAVLT) in discriminating between people with subjective cognitive decline (SCD) and amnestic mild cognitive impairment (aMCI) and convergent validity of the telephone-RAVLT. Method: In total, 83 older adults (age = 71.4 ± 7.0) with SCD or aMCI completed the RAVLT learning trials over the telephone and the Hopkins Verbal Learning Test (HVLT) in-person. Results: Telephone-RAVLT total recall significantly correlated with HVLT total recall ( r  = .49, p  < .001). Significant between group differences were found (effect size = 0.94). Conclusions: This study provides support for known-groups and convergent validity of the telephone-RAVLT.